LEGISLATIVE LANDMARKS: A COMPARATIVE ANALYSIS OF BAHRAIN’S PROGRESS IN WOMEN’S LABOR RIGHTS - Al-Khalifa, Fatima Hassan; Al-Ahmed, Ali Jaber (Ayden International Journal of Law, Political Science, and Administration, 2024)
The increasing participation of women in the labor market is influenced by various factors, including higher educational attainment, evolving labor laws, financial responsibilities, and the shift from traditional to modern means of production. This paper examines these influences and highlights the importance of aligning labor legislation with the reality of women's roles in the workforce, in line with international principles and conventions.